Research results on development and construction of cyclic electron accelerator MT-22 - D, Baararkhuu; B, Sergelen; A.G, Belov (Scientific transaction of the National University of Mongolia. Physics, 2022)
In this paper we have presented the operation of the cyclic electron accelerator- microtron MT-22 which constructed in cooperation with specialists of Joint Institute for Nuclear Research and Mongolia. We are reached the research level results improving the radiation and technical characteristics of the microtron.